2022
DOI: 10.26689/pbes.v5i3.3982
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Impact of Entrepreneurial Learning on the Business Model Innovation of Startups

Abstract: Entrepreneurial learning involves all kinds of learning activities carried out by enterprises in the process of development. It helps entrepreneurs, as the backbone of enterprises, master key entrepreneurial knowledge and solve practical problems encountered in entrepreneurship. It runs through the whole process of entrepreneurial activities. According to research, through entrepreneurial learning, start-ups can improve entrepreneurial opportunities, entrepreneurial dynamics, and other development potentials; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Research worldwide has shown that Entrepreneurial Education is an important driver of innovation and business success (Naushad, 2022). In China, with the development of the market economy and policy support, Entrepreneurial Education is increasingly recognised as a key driver of growth and innovation for SMEs (Chu & Astillero, 2022). Research shows that entrepreneurs who have received high quality Entrepreneurial Education are more likely to achieve rapid business growth and market expansion (Saah, 2022).…”
Section: Entrepreneurial Education and Sme Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Research worldwide has shown that Entrepreneurial Education is an important driver of innovation and business success (Naushad, 2022). In China, with the development of the market economy and policy support, Entrepreneurial Education is increasingly recognised as a key driver of growth and innovation for SMEs (Chu & Astillero, 2022). Research shows that entrepreneurs who have received high quality Entrepreneurial Education are more likely to achieve rapid business growth and market expansion (Saah, 2022).…”
Section: Entrepreneurial Education and Sme Developmentmentioning
confidence: 99%
“…Product and process innovations directly improve firms' productivity and market performance, while organisational and market innovations help firms optimise their management structure and explore new market segments (Naushad, 2022). Empirical studies have shown that improved innovation capabilities are significantly associated with business expansion and sustainable growth of SMEs (Chu & Astillero, 2022).…”
Section: Innovation Capacity As a Competitive Advantagementioning
confidence: 99%
See 2 more Smart Citations